High-amplitude γ Doradus variables. Issue 3 (23rd September 2020) - Paunzen, Ernst; Bernhard, Klaus; Hümmerich, Stefan; Hambsch, Franz-Josef; Lloyd, Christopher; Otero, Sebastián
ABSTRACT: According to most literature sources, the amplitude of the pulsational variability observed in γ Doradus stars does not exceed 0.1 mag in Johnson V . We have analysed fifteen high-amplitude γ Doradus stars with photometric peak-to-peak amplitudes well beyond this limit, with the aim of unraveling the mechanisms behind the observed high amplitudes and investigating whether these objects are in any way physically distinct from their low-amplitude counterparts. We have calculated astrophysical parameters and investigated the location of the high-amplitude γ Doradus stars and a control sample of fifteen low-amplitude objects in the log T eff versus log L / L ⊙ diagram. Employing survey data and our own observations, we analysed the photometric variability of our target stars using discrete Fourier transform. Correlations between the observed primary frequencies, amplitudes and other parameters like effective temperature and luminosity were investigated. The unusually high amplitudes of the high-amplitude γ Doradus stars can be explained by the superposition of several base frequencies in interaction with their combination and overtone frequencies. Although the maximum amplitude of the primary frequencies does not exceed an amplitude of 0.1 mag, total light variability amplitudes of over 0.3 mag ( V ) can be attained in this way. Low- and high-amplitude γ Doradus stars do not appear to be physically distinct in any other respect than their total variability amplitudes but merely represent two ends of the same, uniform group of variables.